2012
DOI: 10.1310/sci1804-315
|View full text |Cite
|
Sign up to set email alerts
|

Functional Electrical Stimulation in Spinal Cord Injury Respiratory Care

Abstract: The management of chronic respiratory insufficiency and/or long-term inability to breathe independently has traditionally been via positive-pressure ventilation through a mechanical ventilator. Although life-sustaining, it is associated with limitations of function, lack of independence, decreased quality of life, sleep disturbance, and increased risk for infections. In addition, its mechanical and electronic complexity requires full understanding of the possible malfunctions by patients and caregivers. Ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…However, there is some evidence to suggest that if there is partial phrenic sparing contralateral to an asymmetric (lateralized) SCI, then combined contralateral phrenic and bilateral intercostal pacing may yield similar functional benefits (DiMarco et al, 2005b). Moreover, effectiveness of diaphragm pacing may be time dependent and only acute post-injury patients may benefit from this intervention (Jarosz et al, 2012). For these reasons, additional reverse-translation studies in animal models are needed to explore mechanisms contributing to diaphragm stimulation and its effects on neuroplasticity, muscle preservation, improvements in general respiration as well as ways to improve existing pacing techniques.…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
“…However, there is some evidence to suggest that if there is partial phrenic sparing contralateral to an asymmetric (lateralized) SCI, then combined contralateral phrenic and bilateral intercostal pacing may yield similar functional benefits (DiMarco et al, 2005b). Moreover, effectiveness of diaphragm pacing may be time dependent and only acute post-injury patients may benefit from this intervention (Jarosz et al, 2012). For these reasons, additional reverse-translation studies in animal models are needed to explore mechanisms contributing to diaphragm stimulation and its effects on neuroplasticity, muscle preservation, improvements in general respiration as well as ways to improve existing pacing techniques.…”
Section: Therapeutically Shaping Respiratory Neuroplasticitymentioning
confidence: 99%
“…The concept of using electrical stimulation to replace external mechanical ventilation goes back as far as the 18th century. 19,23,24 In 1786, Leopold Caldani reported that electrical stimulation of the phrenic nerve could evoke diaphragm contraction and air movement in animals, a finding that was then replicated in a human postmortem in 1818 by Andrew Ure. 25 In 1872, Guillaume-Benjamin-Amand Duchenne similarly reported that passing electrical current through moist sponges placed on the sternocleidomastoid muscles could evoke diaphragm contraction.…”
Section: Origins and State-of-the-art Of Electrophrenic Respirationmentioning
confidence: 99%
“…The devices are designed for lifelong use and may provide interfacing capability with pulse oximetry and carbon dioxide monitoring. 2,24,32,36 Similarly, commercially available DMPP devices, such as the NeuRx RA/4 Respiratory Stimulation System (Synapse Biomedical), are implanted via laparoscopic approach, can achieve equivalent tidal volumes to PNP, and can therefore be considered as a costeffective and low-risk alternative to conventional PNP. 3,23,24,[37][38][39][40][41][42] Although mechanical positive pressure ventilation can provide basic ventilation as a life-sustaining measure, electrophrenic respiration (EPR) produces "active" diaphragm contraction to restore the physiological negative intrathoracic pressure and provide superior ventilation performance.…”
Section: Origins and State-of-the-art Of Electrophrenic Respirationmentioning
confidence: 99%
See 2 more Smart Citations